1996
DOI: 10.1152/ajpendo.1996.270.4.e627
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged bed rest decreases skeletal muscle and whole body protein synthesis

Abstract: We sought to determine the extent to which the loss of lean body mass and nitrogen during inactivity was due to alterations in skeletal muscle protein metabolism. Six male subjects were studied during 7 days of diet stabilization and after 14 days of stimulated microgravity (-6 degrees bed rest). Nitrogen balance became more negative (P < 0.03) during the 2nd wk of bed rest. Leg and whole body lean mass decreased after bed rest (P < 0.05). Serum cortisol, insulin, insulin-like growth factor I, and testosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
343
2
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(389 citation statements)
references
References 12 publications
28
343
2
6
Order By: Relevance
“…While the atrophy of disuse, such as occurs with protracted bed rest is well described (8,10,16) it is less clear cut as to the extent to which variation in levels of physical activity within the normal population influences sarcopenia, mainly because of the difficulty of measurement. Low physical activity at work has been identified as a risk factor for sarcopenia (17) and a recent study indicated that muscle mass and strength in the elderly does respond to aerobic exercise (18) .…”
Section: Inactivity: Energy Intakesmentioning
confidence: 99%
“…While the atrophy of disuse, such as occurs with protracted bed rest is well described (8,10,16) it is less clear cut as to the extent to which variation in levels of physical activity within the normal population influences sarcopenia, mainly because of the difficulty of measurement. Low physical activity at work has been identified as a risk factor for sarcopenia (17) and a recent study indicated that muscle mass and strength in the elderly does respond to aerobic exercise (18) .…”
Section: Inactivity: Energy Intakesmentioning
confidence: 99%
“…Specific disuse-induced changes include a negative nitrogen balance, a decrease in whole body protein synthesis, and an increase in lower-limb proteolysis leading to decreased amounts of contractile protein in skeletal muscle (11,20,44,57,67).…”
mentioning
confidence: 99%
“…O desuso muscular provocado por condições de períodos longos no leito, colocação de órteses ou fixações em membros e microgravidades induzem resistência à insulina e a um estado catabólico nos musculoesqueléticos afetados de humanos 7 . Esse quadro de resistência à insulina pode explicar a redução das reservas de glicogênio inerente à imobilização em todos os músculos analisados nesse estudo.…”
Section: Discussionunclassified
“…A homeostasia metabólica das fibras musculares também pode ser comprometida, induzindo o quadro de resistência à insulina e a um estado catabólico nos musculoesqueléticos afetados de humanos 7,8 . Porém, ainda não está claro como o desuso muscular crônico ou a imobilização alteram a sinalização de insulina 9 .…”
Section: Introductionunclassified